Legal Certainty of Inheritance for Children Born Out of Wedlock Who Are Recognized as Legitimate by Their Biological Parents - Muhammad Ikhlas Bin Rosele Lubis; Laila Rizqillah; Amanda Putri Fajrin; Aulia Putri; Aqtika Deeba Lubis (Jurnal Sahabat ISNU SU, 2024)
The legal status of illegitimate children in Indonesia has become a complex issue involving legal, religious, and social aspects. Illegitimate children often experience discrimination in obtaining civil rights, particularly regarding lineage, maintenance, and inheritance. This study aims to analyze the legal certainty for illegitimate children recognized by their biological parents, focusing on Indonesian positive law regulations, Islamic religious perspectives, and the role of the Constitutional Court. This study also offers comprehensive solutions to overcome legal and social barriers in the implementation of illegitimate child protection policies. This study uses a juridical-normative method with a multidisciplinary approach, combining positive law analysis, Islamic religious studies, and socio-cultural aspects. The results show that Constitutional Court Decision Number 46/PUU-VIII/2010 is a step forward in providing legal recognition for illegitimate children, but its implementation still faces significant challenges. Under Islamic law, the status of illegitimate children tends to be limited to the lineage relationship with their biological mother, although alternatives such as a mandatory will exist to protect their rights. This study recommends regulatory revisions, public outreach, strengthening the role of child protection agencies, optimizing evidentiary technologies such as DNA testing, and harmonizing positive law and Islamic law. With a holistic approach, it is hoped that legal protection for illegitimate children can be implemented fairly, inclusively, and in accordance with humanitarian principles.